Randomised controlled trial of transcutaneous electrical muscle stimulation of the lower extremities in patients with chronic obstructive pulmonary disease. Issue 12 (1st December 2002) - Bourjeily-Habr, G; Rochester, C L; Palermo, F; Snyder, P; Mohsenin, V
Abstract : Background: Although exercise training improves exercise tolerance in most patients with chronic obstructive pulmonary disease (COPD), some patients with severe disease may not be able to tolerate exercise training due to incapacitating breathlessness. Transcutaneous electrical muscle stimulation (TCEMS) has been shown to improve muscle strength, muscle mass, and performance in paraplegics, patients with knee ligament injury, and patients with peripheral vascular disease. We hypothesised that TCEMS of the lower extremities can improve muscle strength and exercise tolerance in patients with moderate to severe COPD. Methods: A randomised controlled trial of TCEMS of the lower extremities was performed in 18 medically stable patients of mean (SD) age 60.0 (1.5) years with a mean forced expiratory volume in 1 second (FEV1 ) of 1.03 (0.10) l (38% predicted) and residual volume/total lung capacity (RV/TLC) of 59 (2)%. Stimulation of the lower extremities was performed three times a week, 20 minutes each session, for six continuous weeks. Quadriceps and hamstring muscle strength, exercise capacity, and peak oxygen uptake were measured at baseline and after 6 weeks of stimulation. Results: TCEMS improved both the quadriceps strength (by 39.0 (20.4)% v 9.0 (8.1)%, p=0.046) and hamstring muscle strength (by 33.9 (13.0)% v 2.9 (4.7)%, p=0.038) in the treated (n=9) and sham treated (n=9) groups, respectively. The improvement in muscle strength carried over to better performance in the shuttle walk test in the treated group (36.1% v 1.6% in the treated and sham groups respectively, p=0.007, Mann-Whitney U test). There was no significant change in lung function, peak workload, or peak oxygen consumption in either group. Muscle stimulation was well tolerated by the patients with no dropouts and better than 95% compliance with the protocol. Conclusions: TCEMS of peripheral muscles can be a useful adjunct to the comprehensive pulmonary rehabilitation of patients with COPD.